2017
DOI: 10.1038/aps.2017.91
|View full text |Cite
|
Sign up to set email alerts
|

GOLPH2-regulated oncolytic adenovirus, GD55, exerts strong killing effect on human prostate cancer stem-like cells in vitro and in vivo

Abstract: GOLPH2 (also called GP73) is a Golgi glycoprotein, which has been identified as a novel tumor marker upregulated in various cancers, including prostate cancer (PCa). GD55 is a novel GOLPH2-regulated oncolytic adenovirus that exhibits a strong killing effect on hepatoma cells. Here, we investigate the antitumor effect of GD55 on prostate cancer stem cell (CSC)-like cells in vitro and in vivo. Prostate CSC-like sphere cells were acquired and enriched by culturing DU145, LNCap or P3 prostate cancer cells in suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…32 Using circRNAs as targeted and other strategies (such as oncolytic adenovirus) may be benefit to improve the treatment of cancers. 33 In summary, hsa_circ_0068669 expression was significantly downregulated in HCC tissues and HCC cell lines. Furthermore, our results indicated that hsa_circ_0068669 might be involved in metastasis of HCC, and it may be a novel biomarker of HCC metastasis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…32 Using circRNAs as targeted and other strategies (such as oncolytic adenovirus) may be benefit to improve the treatment of cancers. 33 In summary, hsa_circ_0068669 expression was significantly downregulated in HCC tissues and HCC cell lines. Furthermore, our results indicated that hsa_circ_0068669 might be involved in metastasis of HCC, and it may be a novel biomarker of HCC metastasis.…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have described that besides serving as miRNA sponge and transcription regulator, circRNAs can be served as mRNA traps via sequestering the translation start site to regulate protein expression . Using circRNAs as targeted and other strategies (such as oncolytic adenovirus) may be benefit to improve the treatment of cancers …”
Section: Discussionmentioning
confidence: 99%
“…Although great progress has been made in the field of oncolytic virotherapy, including cancer ‐targeting gene virotherapy strategy proposed by our group that was based on oncolytic adenovirus using the tumour‐specific promoters instead of E1A promoter to enhance the targeting ability and safety of adenoviruses, 5,22‐24 there are some issues to restrain its application in cancer therapy. First, the heterogeneity of oncolytic adenoviruses may induce an inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Although O Ad .DD3.mK5 showed significant antitumor effects in our study, there are also some limitations to be solved before O Ad .DD3.mK5 can be further used in clinical trials for prostate cancer patients, especially when it is delivered via intravenous injection. The existing limitations mainly include liver damage caused by virus accumulation and the clearance of viral particles by neutralizing antibodies, immune responses against the virus, and the influence of the tumor microenvironment on viral replication [16]. To address these problems, combined treatment with chemoradiotherapy, immunotherapy, packaging or modification via nanoparticles [17] had been used for the treatment of the oncolytic virus.…”
Section: Discussionmentioning
confidence: 99%
“…The tumor volume of the six mice in each group was measured every three days and estimated using the following equation: (length × width2)/2 [12,13]. At the end of the experiment, mice were killed and the tumors were resected for H&E staining and immunofluorescence staining analyses [14, 15, 16].…”
Section: Methodsmentioning
confidence: 99%